2002
DOI: 10.1080/15226510208500084
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Pentachlorophenol in the Crested Wheatgrass (Agropyron cristatum × desertorum) Rhizosphere

Abstract: Pentachlorophenol (PCP) is a widespread, highly toxic contaminant of soil and water that is generally recalcitrant to microbial breakdown and thus may be considered a good candidate for phytoremediation. PCP toxicity and rates of mineralization were compared in crested wheatgrass seedlings that were either sterile or rootinoculated with microbial consortia derived from soil at a PCP-contaminated site. Inoculated seedlings were more tolerant to PCP and mineralized threefold more 14 C-PCP than sterile seedlings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…'Hycrest' crested wheatgrass [Agropyron desertorum (Fischer ex Link) Schultes] accelerated the degradation of pentachlorophenol (PCP), a compound used to treat lumber to prevent rot, in contaminated soil with 36% of the PCP absorbed by the plants and 22% mineralized (Ferro et al, 1994). Subsequent research found that microbes in the rhizosphere were responsible for mineralizing the PCP (Miller and Dyer, 2002). While the specifi c microbes were not identifi ed, experiments indicated that root exudates from the wheatgrass helped recruit PCP-degrading microbes and served as co-metabolites to enhance PCP degradation.…”
Section: Land Reclamation Bioremediationmentioning
confidence: 99%
“…'Hycrest' crested wheatgrass [Agropyron desertorum (Fischer ex Link) Schultes] accelerated the degradation of pentachlorophenol (PCP), a compound used to treat lumber to prevent rot, in contaminated soil with 36% of the PCP absorbed by the plants and 22% mineralized (Ferro et al, 1994). Subsequent research found that microbes in the rhizosphere were responsible for mineralizing the PCP (Miller and Dyer, 2002). While the specifi c microbes were not identifi ed, experiments indicated that root exudates from the wheatgrass helped recruit PCP-degrading microbes and served as co-metabolites to enhance PCP degradation.…”
Section: Land Reclamation Bioremediationmentioning
confidence: 99%
“…Wheatgrass removed PCP from soil (Miller and Dyer, 2002) and rice showed the ability to remove 2,4-DCP from nutrient solutions (Su and Zhu, 2006). It has also been shown that wheat is able to take up 2,4-DCP from aqueous solutions with an efficiency of almost 20%.…”
Section: Introductionmentioning
confidence: 97%
“…Wheatgrass and ryegrass removed pentachlorophenol from soil (Miller and Dyer 2002;He et al 2005). Chlorella and rice showed the ability to remove 2,4-dichloropenol from nutrient solutions (Scragg et al 2003;Su and Zhu 2006).…”
Section: Introductionmentioning
confidence: 99%